(untitled) (Fiep Bulletin - online, 2014)
This study aims at describing and interpreting the evaluation offered by engaged and disengaged children of the Esporte Cidadão Social Project, which is anchored in sports and physical activities and developed in a low-income urban community in Vila Velha, ES. The answers were obtained from 83 adolescents, boys and girls, from which 14 are still engaged on such activities whereas 69 left the project. Based on Hirschman (1970), we evaluated voice power and engagement of these two groups as well as the effect of their reaction to the inadequacy of the project, leading them to give up sports and physical activities. The analysis of the answers revealed that the social has project partially failed to achieve its member’s aims, since there wasn’t enough space for competition and other kinds of challenge, since the main activities were concentrated on recreation, leisure, and education for active citizenship. The results of the analysis pointed to a need for reorientation of the project towards more leisure activities, internal and external competitions, without abandoning critical reflection activities. This research main conclusion is that social projects coordinators must evaluate the interests and perspectives of the community they intend to intervene in and must offer challenging activities able to meet participants’ goals.